Youth participation in religious activities and nation character development in Indonesia - Elly Yuliawati, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Almost every religion involves youth participation in activities; signifying growing awareness of the need for youths in the continuity of religious practices and vice versa, as young people depend on religion as a basis for good character in facing the challenges of their time. This study examines youth participation in understanding religion, especially Islam, and why participating in religious activities establishes itself in the context of migratory or young migrants. In doing so, this study explores the what, why and how forms of youth participation in such religious activities contribute to the development of national character. Further to this, youth participation in the Hijrah Fest is in line with the theory of a relational development system where relationships that occur between individuals such as youths in particular strengthen each other to form an independent hijrah community. Using qualitative methods, this study found that the Hijrah Fest is a social capital for the community, whose activities encourage many young people to be independent, work together and develop good morals. This is in line with the state's goal of developing the character of Indonesian youth. Hijrah Fest is also supports the vision of the Indonesian government in realizing a sovereign, independent youth personalities through such collaboration.